A Survey Paper on Rural E-marketplace for Local Farmers with Chatbot for Pesticides - Likhith Reddy D; Prajwal Mallappa Sankanur; Kushal K; Deepak N R (Journal of Android and IOS Applications and Testing, 2025)
Rural farmers encounter issues related to market access, crop advisory services, and the safe use of pesticides, resulting in lower income and productivity. The paper proposes the design and evaluation of a smart digital platform for a rural e-marketplace with an integrated AI-powered pesticide-advisory chatbot. The platform consists of mobile and web portals, farmer onboarding, crop listing, real-time pricing, secure payments, geospatial mapping of farms, IoT-based monitoring of crops, and AI-driven personalised and context-specific pesticide and cultivation guidance on a crop-by-crop basis. The study overview background terminologies, illustrate literature, discuss existing trends and challenges facing rural agriculture, introduce the evaluation metrics and benchmarks we developed, and present applications and use-cases. Directions for the future, limitations, and policy considerations are also presented. Overall, the digital platform aims to elevate incomes for farmers, promote safe and sustainable farming practices, and generate empowerment in rural communities.